Moral Property Rights in Bargaining with Infeasible Claims - Gächter, Simon; Riedl, Arno (Management Science, 2005)
In many business transactions, labor-management relations, international conflicts, and welfare-state reforms, bargainers hold strong entitlements that are often generated by claims that are not feasible anymore. These entitlements seem to shape negotiation behavior considerably. By using the novel setup of a “bargaining with claims” experiment, we provide new systematic evidence tracking the influence of entitlements and obligations through the whole bargaining process. We find strong entitlement effects that shape opening offers, bargaining duration, concessions, and (dis)agreements. We argue that entitlements constitute a “moral property right” that is influential independent of negotiators' legal property rights.